Compilation of research outputs BS Psychology III - I SY 2013-2014 - Coronel, Shiela Marie L.. et. al./ Aguilar, Karol Louise et. al. 4 0 16; 5 (2014)
Organizational Commitment, Attchment Style, Job Satifaction - ABSTRACT: The purpose of the present study was to analyze Filipino employees attachment style and organizational commitment and their relation to job satisfaction. The respondents were seventy employees and obtained from the Committee offices of the House of Representatives. A purposive sampling was used for which locale may be described as a quota (non-probability) sample. In order to assess the employee's job satisfaction, attachment style, and organizational commitment, the researchers used the following questionnaires: Job Satisfaction Survey by Paul Spector (Spector, 199), Relationship Scale Quesationnaire by Griffin and Bartholomew (1994), and TCM Employee Commitment Survey by Meyer and Allen (1990). The method that the researchers used to compute for the data is Pearson's r at a = 0.05 that measures the correlation between two or more variables and Cronbach for the test of reliability. Based on the results, it was found that there is no significant correlation between the attachment style and job satisfaction of the respondents and neither is there a correlation between the organizational commitment and job satisfaction of each respondent. However, there is a significant correlation between some dimension of organizational commitment and attachment styles.;Organizational Commitment as an Indicator of Job Satisfaction among Employees-ABSTRACT: The principal purpose of this research is to determine if the Filipino workforce are more likely to manifest an affective organizational commitment and are satisfied with their job, with Filipino's emotionality as basis. The participants of the research were fifty (5) regular employees from Housing and Urban Development Coordinating Council (HUDCC) that were chosen with the use of purposive sampling. The researchers made use of two instruments namely Job Satisfaction Survey (JSS( by Paul E. Spector and TCM Employee Commitment Survey Academic Users Guide 2004 by John P. Meyer and Natalie J. Alllen. The data gathered were then analyzed by Single-factor Analysis of Variance (ANOVA) at a = 0.05. The results indicated that there is a variety between gender as to what organizational commitment and level of satisfaction each gender possess. Contradicting to the claim of the study, it was found out that the most prevalent organizational commitments among employees of HUDCC tend to be affective and continuance commitments and are likely to have an ambivalent level satisfaction.
Undergraduate Thesis: (B.S. Psychology) - Pamantasan ng Lungsod ng Maynila, 2014.;.Content: Organizational Commitment, Attachment Style, Job Satisfaction.;.Content:Organizational commitment as an indicator of job satisfaction among Employees.
Keywords: 2 -- 0; 6; 20; 20; 2